An Analysis of Ethical Theories in the Direction of Sustainable Development: Aristotelian Virtue Ethics is the Greatest Option for Long-term Sustainability - Maharana, Subhasmita; Behura, Ajit Kumar (Problemy Ekorozwoju, 2023)
Environmental issues such as deforestation, climate change, ozone layer depletion, greenhouse effect, and pollution of air, water, and soil are among the most difficult to address. These are the results of human beings’ immoral actions. Humans are the most powerful living beings on the planet, and they have abused their physical and mental abilities to fulfill their greed rather than their needs, resulting in environmental destruction. They have abused nature and exploited it for their own economic gain, giving them control over it. Furthermore, environmental degradation and human moral decline are intertwined, necessitating a moral revolution to reform human conduct for the sake of society, with a focus on Aristotelian Virtue Ethics rather than consequentialist or deontological ethics. The main focus of Aristotelian Virtue Ethics is, on what type of persons we should be, what kind of characteristics we should have, and how we should act. This leads to the development of one’s character and environmental attitudes; resulting in the smart use of natural resources and, more particularly, the preservation of the natural environment, ensuring environmental sustainability.